Open Access and the Economics of Scholarshipin Rhetoric and Composition Studies. Issue 2 (3rd April 2018) - Edwards, Mike; Reyman, Jessica
Abstract : Rhetoric and composition, as an academic discipline, argues for a strong link between scholarship and practice. However, restrictive publisher agreements, limited distribution channels, and perceptions about the value of open access among gatekeepers can limit access to scholarship and its potential for application. This study, through analysis of publishing policies and practices for rhetoric and composition journals as well as surveys and interviews with journal editors, examines the current state of open access in the field. Findings reveal the need for more consistent and widespread adoption of more open policies for publishing to extend the impact and value of scholarship in the field.